ISIS:Eastern Violence and Critique of Fascistic Reason: A Critical Look at Method, Content, and the Claims - Ghadir Nasri (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Deliberation on thought and acts of ISIS has an strategic importance. Sources about ISIS are divided into two categories: Narrative sources and deliberative works. ISIS: Eastern Violence and Critique of Fascistic Reason written by Bachtyiar Ali (Tehran: Markaz Publisher, 2015), is a theoretical and philosophical research about entity and origins of ISIS. According to Bachtyar Ali’s analysis, ISIS is the result of capitalism in the east. According to his belief, ISIS are like AL–Qaeda and Baasist groups and we cannot find any important difference between them since ISIS did what AL–Qaeda and Baasist groups have done and other potential groups will do. He relates these intimidating deeds and baseless claims to eternal identity, and believes that eastern wisdom is the source of all these violent acts. He does not explain the nature and mechanism of this innovative concept, but he interprets ISIS with a focus on identity and lunatic patriotism.  This article pays attention to Bakhtiar Ali’s opinions about the aforementioned concepts and reviews his work based on the methodological and theoretical perspectives such as method critique, content critique, and structure critique.